The Influence of User-Generated Content and Company-Generated Content as a Marketing Strategy on Customer Engagement (Case Study on PT Coca-Cola Indonesia Instagram Social Media) - Christopher G. V. H.; Mentiana Sibarani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the influence of User Generated Content (UGC) and Company Generated Content (CGC) as marketing strategies on customer engagement on PT Coca-Cola Indonesia's Instagram. Using observations and questionnaires processed via SPSS, this research involved 105 respondents who had purchased Coca-Cola products and created UGC on Instagram. The research results show that both UGC and CGC have a positive and significant influence on customer engagement. UGC, which includes reviews, photos, videos, and comments from consumers, provides an authentic feel and builds trust and emotional connections with other consumers, thereby increasing engagement. CGC, in the form of advertising, promotional campaigns, and product information from the company, provides structured and high-quality information that supports the company's image. These two types of content complement each other in creating an interactive and dynamic environment, strengthening loyalty, and driving higher brand engagement and conversions.